Taxing versus subsidizing debt under financial frictions - Andreas Schabert (Economic Theory, 2024)
We examine optimal credit market policies in two models with durables/capital as collateral. Pecuniary externalities rationalize ex-ante debt taxes as macroprudential regulation, achieving constrained efficiency. Ex-post debt subsidies can implement first-best by stimulating collateral demand. Due to the same effect, debt subsidies that are constant over time can be superior to debt taxes. Saving subsidies can further enhance efficiency by addressing distributive effects of pecuniary externalities via interest rate reductions. The analysis shows that debt-increasing subsidies can outperform macroprudential regulation, and that constrained inefficiency caused by collateral externalities is insufficient to establish debt taxes as optimal credit market policies.
Keywords: E44; G18; H23; 330; Financial stability; Pecuniary externalities; Collateral constraint; Macroprudential regulation; Distributive effects